Modelling bidirectional modulations in synaptic plasticity: A biochemical pathway model to understand the emergence of long term potentiation (LTP) and long term depression (LTD). (21st August 2016) - He, Yao; Kulasiri, Don; Samarasinghe, Sandhya
Abstract: Synaptic plasticity induces bidirectional modulations of the postsynaptic response following a synaptic transmission. The long term forms of synaptic plasticity, named long term potentiation (LTP) and long term depression (LTD), are critical for the antithetic functions of the memory system, memory formation and removal, respectively. A common Ca 2+ signalling upstream triggers both LTP and LTD, and the critical proteins and factors coordinating the LTP/LTD inductions are not well understood. We develop an integrated model based on the sub-models of the indispensable synaptic proteins in the emergence of synaptic plasticity to validate and understand their potential roles in the expression of synaptic plasticity. The model explains Ca 2+ /calmodulin (CaM) complex dependent coordination of LTP/LTD expressions by the interactions among the indispensable proteins using the experimentally estimated kinetic parameters. Analysis of the integrated model provides us with insights into the effective timescales of the key proteins and we conclude that the CaM pool size is critical for the coordination between LTP/LTD expressions. Highlights: Development of a simplified integrated model of the emergence of synaptic plasticity. The model explains Ca 2+ /calmodulin complex dependent coordination of LTP/LTD expressions. A decline in calmodulin pool size can contribute to cognitive impairment during aging.